FDI In the Indian Economy: Determinants and Impact - Agarwal, Payal (2006)
The purpose of this study is to provide an analysis of the Foreign Direct Investments in India - the various factors that attract investors to India, the impact that such investment has on the domestic economy and the experience of the multinationals with the overall business environment in the sub-continent.